Ultra-flexible perovskite solar cells with crumpling durability: Toward a wearable power source - Lee, Gunhee; Kim, Min Cheol; Choi, Yong Whan; Ahn, Namyoung; Jang, Jihun; Yoon, Jungjin; Kim, Sang Moon; Lee, Jong Gu; Kang, Daeshik; Jung, Hyun Suk; Choi, Mansoo (Energy and Environmental Science, 2019)
Perovskite materials hold great potential as photovoltaic power sources for portable devices owing to their mechanical flexibility and high performance; however, the flexibility and efficiency require further improvement to attain practical viability. We investigated the mechanical fracture behavior of polycrystalline perovskite films by varying the substrate thickness and applying the neutral plane concept. This enabled us to fabricate a crack-free perovskite film on an ultra-thin substrate (∼2.5 μm) and to demonstrate ultra-flexible solar cells with high efficiency (17.03%) with unprecedented flexibility sustained after 10 000 cycles of bending at a 0.5 mm radius. This represents a high efficiency of 13.6% for large-area flexible perovskite solar cells (1.2 cm2), fabricated by using a hybrid transparent electrode composed of a metal mesh grid and conducting polymer. Using a protective layer to achieve the neutral plane concept, our ultra-flexible perovskite solar cells are demonstrated to be durable even after 100 crumpling cycles. Our approach paves the way to fabricate flexible perovskite solar cells for portable power sources.
Keywords: Flexible solar cells; Fracture behavior; Mechanical flexibility; Photovoltaic power; Polycrystalline perovskite; Portable power sources; Protective layers; Substrate thickness